A multifunctional composite hydrogel material and its preparation method and application

By using light-triggered composite hydrogel materials on diabetic ulcer wounds, the photosynthesis and release of oxygen are enhanced by using chloroplast/conjugated polymer nanoparticle complexes, the problems of wound hypoxia and bacterial infection are solved, and wound healing and antibacterial effects are achieved.

CN116813987BActive Publication Date: 2025-03-25SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310690010.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2025-03-25
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

Diabetic ulcer wounds delay healing due to hypoxia. The existing methods rely on gaseous oxygen to maintain sufficient oxygen, and bacterial infection aggravates the wound.

Method used

A multifunctional composite hydrogel material prepared by phototriggered polymer compounds as the matrix and chloroplast/conjugated polymer nanoparticle complex as functional factors is used to enhance photosynthesis and release oxygen, and has a photodynamic bactericidal effect.

Benefits of technology

The hydrogel material can produce oxygen under ultraviolet irradiation, relieve wound hypoxia, promote angiogenesis, accelerate wound healing, and eliminate bacteria through photodynamic bactericidal action, significantly inhibit E. coli and Staphylococcus aureus.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116813987B_ABST
    Figure CN116813987B_ABST
Patent Text Reader

Abstract

This invention discloses a multifunctional composite hydrogel material, its preparation method, and its applications. The hydrogel is a phototriggered composite hydrogel prepared using a polymer compound as the matrix material and a chloroplast / conjugated polymer nanoparticle complex as the functional factor, through a phototriggered chemical crosslinking method. This invention expands the photosynthetically effective radiation range by coating the chloroplast surface with conjugated polymer nanoparticles. These conjugated polymer nanoparticles have a light absorption range including the ultraviolet region, accelerating the electron transport rate in chloroplast photosystem II, enhancing chloroplast photosynthesis, and releasing more oxygen to promote angiogenesis. Furthermore, the generated oxygen sensitizes the polymer nanoparticles to produce reactive oxygen species, which combat bacterial infection in wounds. This composite hydrogel material can achieve multiple functions including in-situ injection, oxygen production, and photodynamic sterilization, showing great promise for wound healing and treatment of infectious diabetic ulcers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new medical materials, and specifically relates to a multifunctional composite hydrogel material and a preparation method and application thereof. Background Art

[0002] Diabetic ulcer (DU) is a major cause of non-traumatic lower limb amputation and a chronic skin complication of diabetes. Researchers have demonstrated that delayed healing of chronic diabetic wounds is the result of damaged neovascularization in the hypoxic response. During wound healing, the wound is locally in a state of hypoxia due to increased demand for O2, peripheral vascular circulation disorders, infection, and local inflammatory cells consuming a large amount of oxygen for respiratory bursts. Therefore, reducing hypoxia in chronic wounds is an urgent problem to be solved in the clinic of diabetes. In addition, bacterial infection worsens, impairing the proliferation of local vascular endothelial cells (VECs), leading to the formation of chronic wounds. However, existing methods mainly rely on gaseous oxygen as an oxygen source, resulting in the inability to maintain sufficient oxygen at the wound site.

[0003] As an organelle, chloroplasts mainly convert light energy into chemical energy, such as adenosine triphosphate (ATP) and biomass, by performing photosynthesis. The main process of photosynthesis is completed by the protein complexes photosystem I (PSI) and photosystem II (PS II) in chloroplasts, which decompose water to eventually produce oxygen and ATP, accompanied by the conversion of nicotinamide adenine dinucleotide phosphate (NADP) to reduced nicotinamide adenine dinucleotide phosphate (NADPH). However, during photosynthesis, the range of light absorbed by chloroplasts is limited to the visible spectrum. In order to increase the light capture of chloroplasts, various light-harvesting nanomaterials can be used to convert poorly absorbed ultraviolet light into highly absorbed visible light to improve the light conversion efficiency of chloroplasts. Conjugated polymers (CPs), as a new type of fluorescent material, have unique light-harvesting capabilities, including the less absorbed ultraviolet part of chloroplasts, which can quickly transfer excitons to nearby low-energy acceptors, similar to the energy transfer between antenna pigments in photosynthesis. All photosynthetic pigments, whether chlorophylls, carotenoids or phycobilins, have long-range conjugated π structures like conjugated polymers. Therefore, conjugated polymers can serve as artificial antennas to compensate for natural antenna pigments and improve photosynthetic efficiency.

[0004] In addition, under light irradiation, conjugated polymers act as good photosensitizers, sensitizing the surrounding oxygen to produce reactive oxygen species (ROS), which are used for antibacterial treatment based on photodynamic therapy (PDT). Cationic conjugated polymers with quaternary ammonium salt groups on the side chains not only have adjustable photophysical properties and good biocompatibility, but can also be adsorbed on the surface of negatively charged bacterial membranes through electrostatic effects, destroying the bacterial membranes and killing the bacteria. Summary of the invention

[0005] The purpose of the present invention is to provide a multifunctional composite hydrogel material for infectious diabetic ulcer wounds, as well as a preparation method and application of the hydrogel, in order to solve the problem of delayed healing of infectious diabetic wounds.

[0006] In view of the above-mentioned purpose, the hydrogel material provided by the present invention is a light-triggered composite hydrogel loaded with chloroplast / conjugated polymer nanoparticle complex prepared by light-triggered chemical crosslinking, using a polymer compound grafted with o-nitrobenzyl alcohol and a polymer compound grafted with cysteine ​​residues as matrix materials and a chloroplast / conjugated polymer nanoparticle complex as a functional factor.

[0007] The conjugated polymer is selected from any one of the following:

[0008]

[0009] Wherein n represents the degree of polymerization of the conjugated polymer, the value of n is an integer of 10 to 30, the value of x is an integer of 2 to 10, R1 is selected from any one of -H, -CN, and -OCH3, and R2 is selected from any one of the following structures:

[0010]

[0011] The value of m is an integer from 2 to 10.

[0012] The above-mentioned polymer compound includes but is not limited to any one of hyaluronic acid (HA), carboxymethyl cellulose (CMC), chitosan, and polylactic acid and glycolic acid.

[0013] The above-mentioned chloroplasts include but are not limited to any one of photosynthetic organisms such as spinach, green radish, Arabidopsis thaliana and photosynthetic bacteria such as cyanobacteria.

[0014] The mass ratio of chloroplast to conjugated polymer structural unit in the chloroplast / conjugated polymer nanoparticle complex is 1:1.5-2.

[0015] The preparation method of the multifunctional composite hydrogel material of the present invention comprises the following steps:

[0016] (1) dissolving a conjugated polymer in tetrahydrofuran (THF), adding the solution to deionized water for ultrasonic treatment for 10 to 20 minutes under ice bath ultrasonic conditions, wherein the volume ratio of tetrahydrofuran to deionized water is 1:4 to 20, then passing nitrogen through the resulting solution to remove THF, and heating and concentrating the solution to obtain a conjugated polymer nanoparticle solution;

[0017] (2) mixing the conjugated polymer nanoparticle solution and the chloroplast suspension at 4° C. to obtain a chloroplast / conjugated polymer nanoparticle complex solution;

[0018] (3) adding dropwise a solution of a polymer compound grafted with o-nitrobenzyl alcohol (NB) having a mass fraction of 5% to 10% to a solution of a polymer compound grafted with cysteine ​​residues (L) having a mass fraction of 5% to 10% at a volume ratio of 1:1 to obtain a polymer compound pre-liquid;

[0019] (4) adding the chloroplast / conjugated polymer nanoparticle complex solution prepared in step (2) to the polymer compound pre-solution obtained in step (3), mixing the mixture, and curing the mixture under ultraviolet light to obtain a multifunctional composite hydrogel material.

[0020] In the above step (2), preferably, the mass ratio of the chloroplasts in the chloroplast suspension to the conjugated polymer structural units in the conjugated polymer nanoparticle solution is 1:1.5-2.

[0021] In the above step (3), the solvent used for the solution of the polymer compound is Dulbecco's phosphate buffered saline (D-PBS) with a pH of 7.4 or deionized water.

[0022] In the above step (4), the volume ratio of the chloroplast / conjugated polymer nanoparticle complex solution to the polymer compound pre-solution is preferably 1:3-5.

[0023] In the above step (4), the UV light intensity is preferably 4 to 20 mW / cm 2 , UV lamp curing time is 10 to 60 minutes.

[0024] The multifunctional composite hydrogel material of the present invention can be used to prepare medicine for treating infectious diabetic ulcer wounds.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention introduces a polymer compound with high biocompatibility and good biodegradability as a carrier material, and uses a chloroplast / conjugated polymer nanoparticle complex as a functional factor. Under ultraviolet irradiation, a rapid sulfur-nitroso reaction occurs between the nitroso group generated by the o-nitrobenzyl alcohol on the polymer side chain and the thiol group on another polymer side chain to form a light-triggered composite hydrogel loaded with the chloroplast / conjugated polymer nanoparticle complex in situ. At the same time, at the interface between the colloid and the tissue, the photogenerated aldehyde group generated by the o-nitrobenzyl alcohol and the amino group on the tissue undergo a double cross-linking reaction of aldehyde-imine cross-linking, so that the gel network and the tissue are quickly fixed. The conjugated polymer nanoparticles have a wide light absorption range including the ultraviolet part. By coating the conjugated polymer nanoparticles on the chloroplast surface to accelerate the electron transfer rate in the chloroplast photosystem II, the photosynthesis of the chloroplast is enhanced and more oxygen is released, which is used to relieve wound hypoxia and promote angiogenesis; in addition, the conjugated polymer nanoparticles have excellent photodynamic sterilization effects. The oxygen generated by the hydrogel can sensitize the polymer nanoparticles to produce active oxygen, relieve wound hypoxia, promote angiogenesis, accelerate wound healing, and eliminate bacteria through photodynamic sterilization to prevent further infection of the wound. The composite hydrogel material of the present invention has a significant inhibitory effect on Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus), can achieve multiple effects of in situ injection, oxygen production, and photodynamic sterilization, and has a good application prospect in wound healing and wound treatment of infected diabetic ulcers.

[0027] BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 These are the UV absorption and fluorescence emission spectra of conjugated polymer nanoparticles (PFE-1-NPs) and chloroplasts.

[0028] Figure 2 1 is a scanning electron micrograph of PFE-1-NPs, chloroplasts, and the chloroplast / conjugated polymer nanoparticle complex (PFE-1-NPs@cp) prepared in Example 1.

[0029] Figure 3 This is a photograph of the composite hydrogel material (HA-L-NB / PFE@cp hydrogel) prepared in Example 1.

[0030] Figure 4 This is a characterization diagram of PFE-1-NPs@cp prepared in Example 1 promoting cell migration and microtubule formation. In the figure, the experimental conditions are all high-glucose culture, Normoxia is the normoxic group, Hypoxia is the hypoxic group, and Hypoxia+Light is 4mW / cm under hypoxic conditions. 2 395nm LED light treatment for 30min.

[0031] Figure 5The bactericidal properties of PFE-1-NPs@cp and HA-L-NB / PFE@cp hydrogels prepared in Example 1.

[0032] Figure 6 This is the experimental result that the HA-L-NB / PFE@cp hydrogel prepared in Example 1 promotes wound healing in diabetic mice. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0034] Example 1

[0035] This embodiment provides a multifunctional composite hydrogel material, the preparation process is as follows Figure 1 As shown, the preparation method specifically comprises the following steps:

[0036] (1) 300 μL of an aqueous solution of a conjugated polymer (PFE-1) having a structural unit concentration of 1.06 mg / mL was added to 4.7 mL of THF and mixed well. The solution was quickly added to 20 mL of deionized water under ice bath ultrasound conditions, and the solution was ultrasonically treated for 10 min. The THF was removed by N2, and the solution was concentrated to 5 mL by heating to 90° C. to obtain a conjugated polymer nanoparticle solution (PFE-1-NPs) having a structural unit concentration of 64 μg / mL. The molecular weight of the structural unit of PFE-1 was 732.7, and the structural formula was as follows:

[0037]

[0038] (2) At 4°C, 1 mL of 64 μg / mL PFE-1-NPs and 1 mL of 40 μg / mL chloroplast (cp) suspension (prepared with sucrose buffer solution) were mixed and shaken for 6 h to obtain a chloroplast / conjugated polymer nanoparticle complex solution (PFE-1-NPs@cp);

[0039] (3) 133 mg of hyaluronic acid grafted with o-nitrobenzyl alcohol (HA-NB) and 133 mg of hyaluronic acid grafted with cysteine ​​residues (HA-L) were dissolved in 2 mL of Dulbecco's phosphate buffered saline (D-PBS, pH 7.4), and the two solutions were mixed at a volume ratio of 1:1 to obtain a HA-L-NB preformed solution; wherein the HA-NB and HA-L were prepared according to the method described in the literature "Promoting Oral Mucosal Wound Healing with a Hydrogel Adhesive Based on a Phototriggered S-Nitrosylation Coupling Reaction";

[0040] (4) Add 500 μL of PFE-1-NPs@cp to 1.5 mL of HA-L-NB preformed solution, mix well, and irradiate with 395 nm LED ultraviolet light at an intensity of 10 mW / cm 2 , irradiated for 30 min, and obtained HA-L-NB / PFE@cp hydrogel.

[0041] Depend on Figure 1 It can be seen that PFE-1-NPs exhibit strong ultraviolet absorption at the maximum absorption wavelength of 393nm, while chloroplasts exhibit extensive absorption in the blue and red fluorescence regions at 350-500nm and 630-680nm, respectively. The fluorescence emission range of PFE-1-NPs is located in the range of 400-524nm, which has a good overlap with chloroplasts. Figure 2 It can be seen that the cationic quaternary ammonium salt groups of PFE-1-NPs bind to chloroplasts through electrostatic interactions, and some nanoparticles are clearly observed to be attached to the surface of chloroplasts, indicating that PFE-1-NPs are successfully coated on the chloroplasts. Figure 3 The results showed that the HA-L-NB preformed solution could be instantly double-crosslinked before and after light irradiation to form a hydrogel.

[0042] Example 2

[0043] (1) 300 μL of a conjugated polymer (PFP) aqueous solution with a structural unit concentration of 1.06 mg / mL was taken and mixed with 4.7 mL of THF, and then quickly added to 20 mL of deionized water under ice bath ultrasonic conditions, and ultrasonicated for 10 min. THF was removed by N2, and the solution was concentrated to 5 mL by heating to 90° C. to obtain a conjugated polymer nanoparticle solution (PFP-NPs) with a structural unit concentration of 64 μg / mL. The structural unit molecular weight of the PFP is 684.6, and its structural formula is as follows:

[0044]

[0045] (2) At 4°C, 1 mL of the above 64 μg / mL PFP-NPs and 1 mL of 40 μg / mL chloroplast (cp) suspension (prepared with sucrose buffer solution) were mixed and shaken for 6 h to obtain a chloroplast / conjugated polymer nanoparticle complex solution (PFP-NPs@cp);

[0046] (3) 133 mg of carboxymethyl cellulose grafted with o-nitrobenzyl alcohol (CMC-NB) and 133 mg of hyaluronic acid grafted with cysteine ​​residues (CMC-L) were dissolved in 2 mL of Dulbecco's phosphate buffered saline (D-PBS, pH 7.4), respectively, and the two solutions were mixed at a volume ratio of 1:1 to obtain a CMC-L-NB preformed solution;

[0047] (4) Add 500 μL of PFP-NPs to 1.5 mL of CMC-L-NB preformed solution, mix well, and irradiate with 395 nm LED ultraviolet light at an intensity of 10 mW / cm 2 , irradiated for 30 min, and obtained CMC-L-NB / PFP-NPs hydrogel.

[0048] Example 3

[0049] The PFE-1-NPs@cp prepared in Example 1 was tested for cell proliferation and angiogenesis ability, and the specific experiments and experimental results are as follows:

[0050] (1) Cell migration assay

[0051] HUVECs cells from the logarithmic growth phase were cultured at 2×10 5 After the cells adhered to the wall and formed a monolayer, a 10 μL pipette was used to draw a line vertically on the bottom of the well plate, and the suspended cells were washed with PBS to remove the suspended cells. The scratched area was photographed with an optical microscope at 0 h. The culture medium was then replaced with a serum-free high-glucose culture medium containing Chloroplast or PFE-1-NPs@cp at 4 mW / cm 2 Irradiate with light for 30 minutes. Immediately place in an oxygen-deficient environment and continue culturing for 24 hours. Record the photographed location and photograph the scratched location using an optical microscope.

[0052] (2) Transwell cell chamber experiment

[0053] HUVECs cells were resuspended in high glucose medium and cultured at 1 × 10 5100 cells / well were inoculated into the upper chamber of the Transwell chamber. After adding Chloroplast or PFE-1-NPs@cp to the lower chamber along the wall, the cells were treated with light and non-light. After being quickly transferred to the hypoxic box for incubation for 24 hours, the chamber was removed and the culture medium was carefully aspirated and transferred to a new 24-well plate. The cells were fixed with 600 μL 4% paraformaldehyde for 30 minutes, the fixative was aspirated, and the cells were washed twice with calcium-free PBS. Subsequently, anhydrous methanol was added to the chamber to permeate the cells for 20 minutes, the methanol was aspirated, and the cells were washed three times with calcium-free PBS. 0.1% crystal violet was added for staining for 15 minutes, and PBS was used to wash the cells three more times. After gently wiping the non-migrated cells in the upper chamber with a cotton swab, the cells were placed under an inverted fluorescence microscope, and the migration of HUVECs cells was evaluated by the migrating cells in five randomly selected areas / wells under high magnification.

[0054] (3) Microangiogenesis experiment

[0055] Mix the matrix gel with a pre-cooled pipette tip, add the matrix gel to the pre-cooled 24-well plate at 250 μL / well and evenly spread it, place it in a 37°C, 5% CO2 cell culture incubator and incubate it for 1 hour, then the plate can be used. After culturing HUVECs cells to the third generation, they were used for angiogenesis experiments. While the matrix gel is solidifying, prepare the cell suspension, digest the cells in the culture dish, resuspend them in DMEM medium, and count them. Use ECM special medium to adjust the cell density to 5×10 4 100 μL / well, add 600 μL of cell suspension to the lower chamber of the culture plate coated with matrix gel. Prepare 200 μL of cell reagent mixture (Chloroplast, PFE-1-NPs@cp) of different experimental groups and add it to the upper chamber, and then treat with light and no light respectively, place in anoxic environment and continue to incubate for 3 hours, then restore to normoxia for 3 hours, observe the formation of tube lumen, and take pictures for record analysis.

[0056] Depend on Figure 4 As can be seen from A and B, under normoxic conditions, the tubular networks of the blank group and the PFE-1-NPs@cp group were very dense, and the length of the tubules was long. In contrast, under hypoxic conditions, these two groups had very few branch points and the network structure was not obvious. However, the number of branch points and angiogenesis observed in the PFE-1-NPs@cp+Light group increased significantly, and the length of the tubules was longer. Further quantification of the angiogenesis length of each group showed that the hypoxic group had fewer mature branch points and capillary-like structures, indicating that hypoxia can significantly inhibit the angiogenesis potential of cells. In contrast, the length of tube formation in the PFE-1-NPs@cp+Light group in the hypoxic group was 495±27μm, which was significantly different from the control group in the hypoxic group. The above results show that at the cellular level, the PFE-1-NPs@cp+Light group can produce oxygen and has the potential to promote microangiogenesis.

[0057] Depend on Figure 4 As can be seen from C and D, under high glucose conditions, compared with the normoxic group, the number of HUVECs cells passing through the Transwell membrane in the hypoxia group was significantly reduced, and the cell migration ability was greatly weakened. In contrast, the number of cells in the PFE-1-NPs@cp+Light group was significantly greater (compared with the non-illuminated group).

[0058] Depend on Figure 4 E and F show that in the scratch test, to ensure that migration is not caused by cell proliferation, the cells were starved 24 h before injury and treatment to minimize cell proliferation. Under hypoxic conditions, the wound distance of the PFE-1-NPs@cp+Light group almost disappeared after 24 h. By quantifying the area of ​​cell migration, the cell migration rate of the PFE-1-NPs@cp+Light group was 69±0.03%, which was higher than that of the blank group (migration rate was 63±0.07%).

[0059] The PFE-1-NPs, PFE-1-NPs@cp, and HA-L-NB / PFE@cp hydrogels prepared in Example 1 were subjected to antibacterial tests. The experimental method was as follows: a mixed solution of reagent bacteria of different components (blank group, PFE-1-NPs group, PFE-1-NPs@cp group, and HA-L-NB / PFE@cp group) was prepared. The bacterial concentration was 1×10 7 CFU / mL. 2 , 30min) and non-light treated, then smeared on agar plates and incubated at 37°C for 24h, and then photographed and counted.

[0060] Depend on Figure 5 It can be seen that compared with the non-illumination group, only very few E. coli and S. aureus colonies were observed in the illumination group of PFE-1-NPs@cp, PFE-1-NPs and HA-L-NB / PFE@cp. Quantitative calculations show that when PFE-1-NPs@cp and HA-L-NB / PFE@cp are present under non-illumination conditions, the survival rates of E. coli are 99.6% and 47.5%, respectively, and the survival rates of S. aureus are 88.6% and 14.6%, respectively. The results show that PFE-1-NPs@cp has almost no bactericidal effect under non-illumination conditions, while HA-L-NB / PFE@cp has a certain bactericidal effect, and its bactericidal effect is mainly due to the antibacterial ability of the biomacromolecule HA. After light treatment (395nm, 4mW / cm 2, 30min), the survival rates of E. coli in the PFE-1-NPs@cp group and HA-L-NB / PFE@cp group were 8.8% and 0.3%, and the survival rates of S. aureus were 4.1% and 0.7%, respectively, indicating that under light conditions, the reactive oxygen species produced by PFE-1-NPs effectively killed the bacteria. In contrast, HA-L-NB / PFE@cp hydrogel could significantly inhibit the growth of bacterial colonies and had more effective antibacterial properties.

[0061] The PFE-1-NPs, PFE-1-NPs@cp, and HA-L-NB / PFE@cp hydrogels prepared in Example 1 were tested for in vivo therapeutic effects, respectively, and the experimental methods were as follows:

[0062] (1) Establishment of STZ-induced diabetic mice and infectious chronic wound model: 5- to 6-week-old female BALB / c mice were fed a high-fat diet for 3 weeks and then fasted for 12 h before being intraperitoneally injected with 100 mg / kg STZ. The fasting blood glucose concentration of the mice was measured using a blood glucose meter. Mice with blood glucose concentrations higher than 16.7 mM for two consecutive times were considered diabetic mice.

[0063] (2) The mice were randomly divided into groups, given 50 μL of different samples and light, and pictures of the wound conditions were collected every 3 days. DM refers to diabetic mice, and DM+Light refers to diabetic mice given samples and light at 4 mW / cm 2, 395nm LED light treatment for 30 minutes. On the 12th day after treatment, the wounds treated with HA-L-NB / PFE@cp in the DM+Light group were almost 100% healed, which was significantly better than other groups. This shows that the HA-L-NB / PFE@cp hydrogel formed by light can significantly promote the healing of diabetic rat wounds.

[0064] like Figure 6 As shown, compared with the non-light-exposed group of DM, the wounds treated with PFE-1-NPs, PFE-1-NPs@cp, and HA-L-NB / PFE@cp in the DM+Light group healed significantly faster starting from the 7th day of treatment. There was no significant difference between the control group and the HA-L-NB / PFE@cp group in the DM group. Compared with the wounds of untreated diabetic mice, the wounds in the HA-L-NB / PFE@cp+Light group healed significantly faster and fully recovered on the 12th day after injury, while the wounds in the other groups were still visible.

Claims

1. A multifunctional composite hydrogel material, characterized in that: The hydrogel material is a light-triggered composite hydrogel loaded with chloroplast / conjugated polymer nanoparticle complex prepared by light-triggered chemical cross-linking, using a macromolecular compound grafted with o-nitrobenzyl alcohol and a macromolecular compound grafted with cysteine ​​residues as matrix materials and a chloroplast / conjugated polymer nanoparticle complex as a functional factor; The conjugated polymer is selected from any one of the following: Wherein n represents the degree of polymerization of the conjugated polymer, the value of n is an integer of 10 to 30, the value of x is an integer of 2 to 10, R1 is selected from any one of -H, -CN, and -OCH3, and R2 is selected from any one of the following structures: The value of m is an integer from 2 to 10; The polymer compound is any one of hyaluronic acid, carboxymethyl cellulose, chitosan, and polylactic acid and glycolic acid.

2. The multifunctional composite hydrogel material according to claim 1, characterized in that: The chloroplasts are derived from any one of spinach, green radish, Arabidopsis thaliana and cyanobacteria.

3. The multifunctional composite hydrogel material according to claim 1, characterized in that: The mass ratio of chloroplast to conjugated polymer structural unit in the chloroplast / conjugated polymer nanoparticle complex is 1:1.5-2.

4. A method for preparing the multifunctional composite hydrogel material according to any one of claims 1 to 3, characterized in that: The method consists of the following steps: (1) dissolving a conjugated polymer in tetrahydrofuran, adding the mixture to deionized water for ultrasonic treatment for 10 to 20 minutes under ice bath ultrasonic conditions, wherein the volume ratio of tetrahydrofuran to deionized water is 1:4 to 20, then passing nitrogen gas through the resulting solution to remove the tetrahydrofuran, and heating and concentrating the solution to obtain a conjugated polymer nanoparticle solution; (2) mixing the conjugated polymer nanoparticle solution and the chloroplast suspension at 4° C. to obtain a chloroplast / conjugated polymer nanoparticle complex solution; (3) adding dropwise a solution of a polymer compound grafted with o-nitrobenzyl alcohol having a mass fraction of 5% to 10% to a solution of a polymer compound grafted with cysteine ​​residues having a mass fraction of 5% to 10% at a volume ratio of 1:1 to obtain a polymer compound preformed solution; (4) adding the chloroplast / conjugated polymer nanoparticle complex solution prepared in step (2) to the polymer compound pre-solution obtained in step (3), mixing the mixture, and curing the mixture under ultraviolet light to obtain a multifunctional composite hydrogel material.

5. The method for preparing the multifunctional composite hydrogel material according to claim 4, characterized in that: In step (2), the mass ratio of the chloroplasts in the chloroplast suspension to the conjugated polymer structural units in the conjugated polymer nanoparticle solution is 1:1.5-2.

6. The method for preparing the multifunctional composite hydrogel material according to claim 4, characterized in that: In step (3), the solvent used for the solution of the polymer compound is Dulbecco's phosphate buffered saline with a pH of 7.4 or deionized water.

7. The method for preparing the multifunctional composite hydrogel material according to claim 4, characterized in that: In step (4), the volume ratio of the chloroplast / conjugated polymer nanoparticle complex solution to the polymer compound pre-solution is 1:3-5.

8. The method for preparing the multifunctional composite hydrogel material according to claim 4, characterized in that: In step (4), the UV light intensity is 4 to 20 mW / cm 2 , UV lamp curing time is 10 to 60 minutes.

9. Use of the multifunctional composite hydrogel material according to claim 1 in preparing a medicine for treating infected diabetic ulcer wounds.